﻿The use of complex marketing analysis and QSPR methodology for the necessity of a drug development grounding for the treatment of type 2 diabetes mellitus with increased bioavailability - Inna Kovalevska; Olena Ruban; Alina Volkova; Alla Kotvitska; Alina Cherkashyna (Pensoft Publishers, 2022)
In order to guarantee qualitative medical and pharmaceutical care it is necessary for all participants of the process to provide consistent interconnected actions, including the use of modern approaches in pharmacotherapy, assessment of the urgent needs of the population in medicines (drugs), development and introduction of modern qualitative, safe and effective drugs into the market. Today, one of the key indicators in determining the population's need for drugs is the epidemiological indicators in a particular region and their dynamics. In recent years, the actuality of optimal and effective approaches developing in the prevention and treatment of socially significant diseases, including diabetes mellitus (DM), has been increasingly emphasized at the global level. All actions that are proposed for the development of standardized guidelines, treatment protocols, programs for on-time detection and prevention of diabetes are aimed at forming a system of measures are patient-oriented, based on understanding the patient's problems, lifestyle, habits, income and expenses for treatment, as well as other components associated with achieving optimal results for patients.